2017
DOI: 10.1016/j.jconrel.2017.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Pyrilamine-sensitive proton-coupled organic cation (H+/OC) antiporter for brain-specific drug delivery

Abstract: Blood-brain barrier (BBB) represents the greatest challenge that hampers therapeutic molecules entering the brain. Here, we described a novel brain-specific delivery strategy targeting to pyrilamine-sensitive H/OC antiporter to facilitate therapeutic molecules cross the BBB and penetrate into the brain. In this study, four cyclic tertiary amines were selected as the brain-targeting moieties to modify naproxen (NP), a non-steroidal anti-inflammatory drug. The obtained NP conjugates displayed cell uptake efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…For the in vivo study, cerebral ischemia model was induced by bilateral common carotid artery occlusion according to the previously published methods (Wang et al., 2017 ). All the animals were randomly divided into six groups: sham-operated group, saline group, and the four administration groups ( n = 5) and received an injection of saline or drugs (1 mg/kg, calculated as ibuprofen) through the tail vein.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the in vivo study, cerebral ischemia model was induced by bilateral common carotid artery occlusion according to the previously published methods (Wang et al., 2017 ). All the animals were randomly divided into six groups: sham-operated group, saline group, and the four administration groups ( n = 5) and received an injection of saline or drugs (1 mg/kg, calculated as ibuprofen) through the tail vein.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, non-steroidal anti-inflammatory drugs (NSAIDs) such as ibuprofen, naproxen and indomethacin have been utilized as neuroprotective agents in treating central nervous system (CNS) diseases (Fan et al., 2011 ; Zhao et al., 2014 ; Zheng et al., 2016 ; Wang et al., 2017 ). For instance, ibuprofen could reduce the risk or even delay the onset of CNS diseases (Teema et al., 2016 ), thus would be a promising drug for the treatment of CNS disorders.…”
Section: Introductionmentioning
confidence: 99%
“…For the in vivo study, cerebral ischemia model was induced by bilateral common carotid artery occlusion according to the previously published methods . All the animals were randomly divided into six groups: sham‐operated group, saline group, and the four administration groups ( n = 5) and received an injection of saline or drugs (1 mg/kg, calculated as naproxen) through the tail vein.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, the incidence of degenerative disease, including Alzheimer and Parkinson diseases (AD and PD), has also significantly increased during the past few decades. Numerous studies suggest that NSAIDs (nonsteroidal anti‐inflammatory drugs), such as naproxen, indometacin, and ibuprofen, have been used as neuroprotective agents to treat central nervous system (CNS) diseases . For instance, naproxen would be a potential agent to treat CNS disorders owing to reducing the odds of CNS diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al also reported that the BBB permeability of naproxen was increased by conjugation with compounds having a tertiary amine moiety. 17 These results suggest that the H þ /OC antiporter could be used to deliver a variety of drugs to the brain. Therefore, clarification of the structural features required for efficient recognition by the H þ /OC antiporter is important in order to utilize it effectively as a drug delivery system.…”
Section: Introductionmentioning
confidence: 95%